Características da aprendizagem significativa em proposições expressas por escrito pelos alunos do ensino fundamental: um estudo de conceitos químicos proposto a partir de atividades experimentais. - Bossolani, Keila (2004)
In this study, it was attempted to develop some experimental activities with the objective of extracting and identifying chemical elements from commercial products of low cost and easy access. The developing finality of these practices would be to compound, later on, an instructional material. In the organization of this material content there would be experimental and nonexperimental activities, which, together, would form a group of didactical activities that would allow discussion about some chemical concepts and provide a significative learning. The experiments were developed first in domestic conditions, because the objective was to build practices, which could be applied in any teaching institution, even in school needy of physical and material basic structures. With the support of the Scientific and Cultural Promotion Center (CDCC), the experiments are now developed in this institution of teaching and research. Therefore, the group of experimental activities developed made possible the extraction of chemical elements: calcium, iron from medicines and food. The chemical concept chemical element and others related to it were approached and emphasized in the didactical material, because with the bibliographic research in didactical and paradidactical books, educational cd-roms and children s games, an absence of experimental activities involving such concepts was perceived. For the elaboration of the instructional material a teaching methodology was used in search of trying to insert the students in an active form in the process of teaching-learning, as well as their previous knowledge. This way, it was attempted to elaborate teaching situations in context which privilege the student s participation in the reconstruction of the knowledge. The activities distribution in the didactical material considered the necessary characteristics in a content organization which hopes to achieve a meaningful learning of concepts and the finalization of this material allowed its application along with the students of the Escola de Ensino Fundamental e Médio Educandário Santo Antônio from Bebedouro SP. The classes were taught by myself while teacher-researcher and with the effective cooperation of the Science teacher. For the data collection the express records written by the students and it was attempted to identify in these records the necessary characteristics to the occurrence of a meaningful learning. The analysis of the data expressed by the students revealed the presence of central themes, conceptual hierarchy which goes from the most general and inclusive concepts to the most specific and lower power of inclusioness, correctly articulated generalizations with examples and non-examples, emphasis on the macroscopic and submicroscopic levels of the knowledge, besides the principles of progressive distinguishment and integrative reconciliation. Furthermore, in most of the apprentice s elaborated propositions, the writings show that the sentences were constructions of their own abilities, which reveal evidence that the concept was comprehended. Besides, the propositions were categorized in relation to the macroscopic and submicroscopic levels of concepts and it was realized that the submicroscopic level prevails over the macroscopic one.